A COMPREHENSIVE CASE REPORT ON CHRONIC KIDNEY DISEASE IN A GOLDEN RETRIEVER - Sachin Manoj; M. Chandrasekar; M. Balagangatharathilagar; K. Mounika (Indian Journal of Veterinary and Animal Sciences Research, 2026)
International Renal Interest Society (IRIS) grades canine chronic kidney disease based on proteinuria, blood pressure, serum creatinine, and SDMA (Symmetric   Dimethylarginine).   The   inter-related   structural   and   functional changes associated with canine chronic kidney disease can be used in diagnostic evaluation of kidney injury. Structural alterations can be studied readily with the non-invasive sonographic assessment of kidneys. Increased cortical echogenicity, loss of corticomedullary differentiation, reduced renal size, and irregular renal contour are observed during B-mode ultrasound imaging. The Doppler ultrasound studies supplement the ultrasonic B-mode assessment and enable the evaluation of renal perfusion based on hemodynamics. Doppler studies would allow clinicians to evaluate or define patient’s response to the therapeutic management of chronic kidney disease.